'The Synthesis is in the Machine': An Interview with Silvia Federici. Issue 96 (3rd April 2018) - Elliott, Jane; Franklin, Seb
ABSTRACT: In this interview Marxist feminist theorist Silvia Federici discusses the following: the relationships between accumulation and reproduction; biotechnology; the recent resurgence of social reproduction theory as exemplified by work in Endnotes and Lies ; the mystification of gendered labour; the disciplining of productive bodies; the sites and technologies of primitive accumulation in the present; and the reproduction of feminism and other social movements in the twenty-first century.